(untitled) (Altre Modernità, 2025)
One of the greatest biographical bestsellers of the current 2020s is the story of self – of a young woman who made it – by the woman who would become the first female Prime Minister of the Italian Republic. Her book is intended as an act of revenge in contrast to the widespread storytelling that surrounds her person and her consequent political action; indeed, it is itself an action of political storytelling that preludes electoral success and the assumption of the highest government responsibilities, in a post-Berlusconi perspective. The tautological title I Am Giorgia refers to the individualistic personalism of contemporary Western politics, but it also refers to an ostentatious familiarity of relationship with the addressee, who is thus assured about the author’s familiarity and closeness to what so many ordinary people experience. The discursive act of self-presentation is split between a basic claim of an alternative political identity, distant from the republican constitutional framework, and the sympathetic friendliness that should guarantee the ability to express the will of Italians in government action. The woman question is evoked and abused to be placed at the service of a vision of interpersonal relations that projects the most backward legacies and opacities of the post-fascist far right into the neoliberal capitalist context.